Free Radicals Derived from γ-radiolysis of Water and Aaph Thermolysis Mediate Oxidative Crosslinking of Egfp Involving Tyr-Tyr and Tyr-Cys Bonds: The Fluorescence of the Protein Is Conserved Only Towards Peroxyl Radicals - Aspee-Lamas, A; Barrías-González, P; Mura-Mardones, F; Fuentes-Lemus, E; Fuentes-Lemus, E (Elsevier Inc., 2020)
The enhanced green fluorescent protein (eGFP) is one of the most employed variants of fluorescent proteins. Nonetheless little is known about the oxidative modifications that this protein can undergo in the cellular milieu. The present work explored the consequences of the exposure of eGFP to free radicals derived from γ-radiolysis of water, and AAPH thermolysis. Results demonstrated that protein crosslinking was the major pathway of modification of eGFP towards these oxidants. As evidenced by HPLC-FLD and UPLC-MS, eGFP crosslinking would occur as consequence of a mixture of pathways including the recombination of two protein radicals, as well as secondary reactions between nucleophilic residues (e.g. lysine, Lys) with protein carbonyls. The first mechanism was supported by detection of dityrosine and cysteine-tyrosine bonds, whilst evidence of formation of protein carbonyls, along with Lys consumption, would suggest the formation and participation of Schiff bases in the crosslinking process. Despite of the degree of oxidative modifications elicited by peroxyl radicals (ROO•) generated from the thermolysis of AAPH, and free radicals generated from γ-radiolysis of water, that were evidenced at amino acidic level, only the highest dose of γ-irradiation (10 kGy) triggered significant changes in the secondary structure of eGFP. These results were accompanied by the complete loss of fluorescence arising from the chromophore unit of eGFP in γ-irradiation-treated samples, whereas it was conserved in ROO•-treated samples. These data have potential biological significance, as this fluorescent protein is widely employed to study interactions between cytosolic proteins; consequently, the formation of fluorescent eGFP dimers could act as artifacts in such experiments. © 2020 Elsevier Inc.